Wandering spleen with pancreatic volvulus and associated scimitar syndrome: A rare anomaly detected on computed tomography - Ravi Kumar Varma Kalidindi; Srinivas Metta; Tripura Mandava; Sesha Mohan Debta (Apollo Medicine)
Pancreatic volvulus with wandering spleen and associated scimitar syndrome and sequestrated lung of the right lower lobe is a rare congenital anomaly. Wandering spleen is a rare clinical condition which occurs due to the laxity and absence of normal intraperitoneal ligaments that hold the spleen in its place. Wandering spleen with pancreatic volvulus and associated scimitar syndrome has never been described in the literature to the best of our knowledge. We present the computed tomography of a young female patient who presented with acute pain abdomen.